EVALUATION OF BEHAVIORAL IMPROVEMENT FOR PREVENTING LIVER FLUKES AND CHOLANGIOCARCINOMA IN SI CHOMPHU SUBDISTRICT, SI CHOMPHU DISTRICT, KHONKAEN PROVINCE - Sata, Anurak; Vaiyanont, Salinee (Primary Health Care Journal (Northeastern Edition), 2024)
This study aims to evaluate the effectiveness of behavior modification in preventing liver fluke disease and cholangiocarcinoma. The participants were divided into two groups: Group 1 consisted of 13 government officials and local network partners involved in the implementation, and Group 2 comprised 365 local residents. Data was collected through focus group discussions and questionnaires. The analysis used percentage, mean, standard deviation, and dependent t-test. The findings revealed that participants rated the performance of contextual factors at the highest level (mean = 4.6), input factors at a high level (mean = 4.3), process factors at a high level (mean = 4.4), and outcome factors at a high level (mean = 4.1). Overall, the implementation was rated as high (mean = 4.3). In terms of knowledge about liver fluke disease and cholangiocarcinoma, the majority of the public had high knowledge, with an average score of 12.4, reflecting a 14.3% increase. This increase in knowledge was statistically significant (p-value < .001). Regarding preventive behaviors for liver fluke disease, most participants exhibited high prevention behaviors, with an average score of 19.7, showing a 34.5% increase. This increase in preventive behaviors was also statistically significant (p-value < .001).